Surface and sorption properties of TIO2 nanotubes, synthesized by electrochemical anodization - Serikov, T.M.; Ibrayev, N.Kh.; Smagulov, Zh. (IOP Conf. Series: Materials Science and Engineering, 2016)
Electrochemical anodizing of titanium metal in the fluorine-containing electrolyte was used for production of nanotubes of titanium dioxide. The surface morphology of the films was investigated by scanning electron microscopy. It was found that with increasing anodizing voltage the inner diameter, growth rate and nanotubes interporous distance is increasing. The distribution of pore volume studied by the method of adsorption and desorption of nitrogen. The specific surface area of titanium dioxide films was measured for determine the conditions of anodizing on their changes. The sorption capacity of the films was studied.
Keywords: Surface properties; sorption properties; TIO2 nanotubes; synthesized; electrochemical anodization